THE DEPARTMENT OF COMPARATIVE EDUCATION OF THE INSTITUTE OF PEDAGOGY OF THE NATIONAL ACADEMY OF EDUCATIONAL SCIENCES OF UKRAINE: SCIENTIFIC ATTAINMENTS FOR THE PERIOD OF 25 YEARS - Olena Lokshyna (National Academy of Educational Sciences of Ukraine, 2019)
The aim of the article is to review and evaluate the scientific attainments of the Department of Comparative Education of the Institute of Pedagogy of NAES of Ukraine during 25 years (1991-2016) of its functioning. 1991 was chosen because it signifies the renaming of the Laboratory of Scientific and Educational Information (established in 1971) into the Laboratory of Comparative Education (the Department of Comparative Education since 2015). This has led to the transformation of its very concept. From analysis and dissemination of foreign experience the Department went to comparative studies, identification of general trends with formulation of landmarks/prospects for the Ukrainian education. Based on the analysis of the published works of the Department the author made conclusion about its sound and multidimensional scientific input. It covers all levels of education and presents the advanced experience/topical processes/innovative phenomena of the world countries-leaders. Under globalization, the scholars of the Department of Comparative Education conduct also a supra-national analysis aimed at opening the impact of the international organizations (EU, UNESCO, OECD, etc.) on the development of educational policy in the world and in Europe. In such a way the scholars of the Department of Comparative Education have added value to the development of the national education.